Essential medical facts every clinician should know to prevent medical errors, pass board examinations and provide informed patient care - Taylor, Robert B. (Springer, 2011)
This book presents selected literature-based information clinicians need to know to provide informed patient care and avoid medical misadventures. Facts that can help make us better and safer clinicians include knowing the usefulness of palmar crease pallor in detecting anemia (not reliable), antibiotics that can cause a false positive opiate urine drug screen (fluoroquinolones), and an occasional early clue to testicular cancer (gynecomastia). Of course, keeping up to date on current medical knowledge and being curious about the implications of published research conclusions not only help assure superior clinical performance; they also bolster the preparation for board examinations.